(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The aggregate used in building is currently in low supply. Forty percent of all garbage is generated by the construction industry every year. Landfill problems and other environmental dangers result from this. Several environmental concerns and landfill difficulties can be mitigated by using recycled concrete aggregate in place of natural aggregate. The experimental outcomes of using recycled concrete aggregate as opposed to natural concrete aggregate are presented in this research. In both recycled and ordinary concrete, the fine aggregate is entirely natural. The aggregate was salvaged from the demolition of two buildings in Padappai. The M25 variety of concrete always uses the same w/c ratio, maximum aggregate size, and mix proportion. Strength changes in recycled aggregate concrete are studied when tested at 7, 14, and 28 days